Air pollution has a more deleterious effect on Alzheimer's disease biomarkers in genetic predisposition to larger hippocampal volumes. (20th December 2022) - Vilor‐Tejedor, Natalia; Genius, Patricia; Rodríguez‐Fernández, Blanca; Minguillón, Carolina; Crous‐Bou, Marta; Suárez‐Calvet, Marc; Milà‐Alomà, Marta; Cirach, Marta; Nieuwenhuijsen, Mark; Sunyer, Jordi; Fauria, Karine; Kollmorgen, Gwendlyn; et al.
Abstract: Background: Gene‐environment interactions are important in understanding Alzheimer's disease (AD) etiology. Current research is limited, possibly due to weak effects of individual genetic variants. We analysed interaction between genetics of hippocampal volume, environmental exposures and levels of AD biomarkers in cognitively unimpaired individuals at increased risk of AD. Method: A total of 319 cognitively unimpaired, middle‐age participants from the Alzheimer's and Families (ALFA) study with data for genotyping, environmental exposures, and cerebrospinal fluid (CSF) biomarkers were included. Genome‐wide genotyping was performed using Infinium Neuro Consortium (NeuroChip) Array. Genetic variants that passed a quality control/imputation procedure were used to calculate polygenic risk scores (PRS) using PRSice version 2. Land use regression estimated residential exposure to particulate matter (PM2.5, PM10 ), and nitrogen dioxide (NO2 ). NeuroToolKit robust prototype assays and Elecsys® immunoassays (both Roche Diagnostics International Ltd, Rotkreuz, Switzerland) were used to measure CSF biomarkers, and amyloid positivity was defined as amyloid‐beta(Aβ)42/40 ratio <0.071. Associations between PRSs and environmental factors were investigated and estimated using multiple logistic/linear regression models adjusted for age and sex; CSF biomarkers were included as outcomes. Result: PRS‐hippocampal volume (HV)×PM10 and PRS‐HV×NO2 were significantly associated with p‐tau (p = 0.045 and p = 0.025, respectively) (Figure 1). Individuals at high genetic predisposition for larger hippocampal volumes had lower levels of p‐tau at low levels of air pollution compared to individuals at low/null genetic predisposition; as the level of exposure to PM10 and NO2 increased, higher values of p‐tau were observed compared to low‐risk individuals. Conclusion: Our results showed that air pollution may have a deleterious effect on biological mechanisms of AD, in cognitively unimpaired individuals with higher genetic liability for larger hippocampal volumes. Further research is needed to elucidate the biological mechanism involved in such associations.